Consumer's Surplus when Consumers are Subject to a Time and an Income Constraint - Lyon, Kenneth S. (Review of Economic Studies, 1978)
Journal Article Consumer's Surplus when Consumers are Subject to a Time and an Income Constraint Get access Kenneth S. Lyon Kenneth S. Lyon Utah State University Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 377–380, https://doi.org/10.2307/2297352 Published: 01 June 1978 Article history Received: 01 January 1976 Accepted: 01 June 1977 Published: 01 June 1978